Taxonomic relationships in some Vicia species from Egypt, based on seed morphology and SDS-PAGE of seed proteins - doi: 10.4025/actascibiolsci.v35i4.19345 - Abdel Khalik, Kadry Nabeh; Al Gohary, Iman Hussien (Acta Scientiarum. Biological Sciences, 2013)
The seed morphology and seed proteins of 11 Vicia taxa from Egypt were studied. Macro- and micro-morphological characters, including seed shape, color, size, hilum shape and seed sculpture were described and analyzed. The secondary sculpture of the cell wall varies from papillose in nearly all Vicia species to lophate in V. hirsuta. Further, the seed proteins of studied taxa were investigated by SDS-PAGE and 39 different bands were scored. The similarity analysis based on the SDS-PAGE profile and seed morphology was found to be a useful characteristic for the discrimination of Vicia species both on the subgeneric and the sectional levels. The present study did not acknowledge V. tetrasperma and V. hirsuta as subgenus Ervum. As a result, division of Vicia into two subgenera i.e. Vicia and Cracca, is supported.